Heat-conducting thin polymer-based composite material containing one-dimensional aluminum nitride and modifier thereof and preparation method of heat-conducting thin polymer-based composite material
By introducing one-dimensional aluminum nitride and its modified substances into thin polymer materials, an efficient thermal conductivity network is formed, which solves the strength and toughness problems caused by the high addition of traditional fillers, and the combination of high thermal conductivity, good mechanical properties and light transmittance is achieved.
Patent Information
- Application Number
- CN202510774121.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-11
- Publication Date
- 2025-08-12
AI Technical Summary
When traditional thermal fillers are added to thin polymer materials at high levels, they lead to low strength, poor toughness, poor elasticity, and opaque light, which is difficult to meet the needs of high thermal conductivity, mechanical properties and light transmittance in the fields of motors, circuit components and semiconductor devices.
One-dimensional aluminum nitride and its modified substances are used as thermal fillers. By forming a thermal conductivity network through the upper and lower surfaces in the polymer matrix, an efficient heat conduction path is formed using one-dimensional morphology and large aspect ratio characteristics, and the bonding strength between the filler and the matrix is improved through surface modification treatment.
The thermal conductivity of thin polymer-based composites is significantly improved, while maintaining or improving the strength, toughness, flexibility and light transmittance of the material, reducing thermal resistance, and preventing cracking and oil seepage.
Smart Images

Figure CN120464173A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polymer composite materials, in particular to a thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product and a preparation method thereof. Background Art
[0002] In the fields of electric vehicles, wind power generation, high-speed railways, aerospace, 5G communications, mobile phones, microelectronics and semiconductor devices, thin polymer materials are widely used, including films of polyetheretherketone (PEEK), liquid crystal polymer (LCP), polyimide (PI), polyetherimide (PEI), polyamideimide (PAI), polyphenylene sulfone resin (PPSU), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyfluoroethylene propylene (FEP), polyphenylene sulfide (PPS), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS), polyethylene terephthalate (PET), polycarbonate (PC), polypropylene (PP), silicone resin (SR), paraffin wax (PF), epoxy resin (ER), polyurethane (PU), etc., as well as sheet-like, paste-like and glue-like filling materials and coating materials. These materials mainly play the role of insulation, support, protection and thermal conductivity. This type of thin polymer-based material: the thickness is generally 3mm or less, especially 1mm or less, and especially less than 100μm; it has excellent insulation, strength, temperature resistance, light transmittance and other excellent properties. Due to the low thermal conductivity of polymer materials themselves, they cannot meet the needs of scenarios where heat dissipation is required, such as the insulation lining of motors, circuit substrates, display screens, thermal interface materials of components such as chips, and protective layers of copper or aluminum cables, heat sinks, etc. In order to make such thin polymer materials have good thermal conductivity, a certain amount of thermal conductive filler is usually added to such polymer materials. Conventional thermal conductive fillers include powders of aluminum oxide (Al2O3), zinc oxide (ZnO), aluminum nitride (AlN), boron nitride (BN), silicon nitride (Si3N4), aluminum (Al), etc. as thermal conductive fillers to improve their thermal conductivity. Chinese invention patent publication number CN118359449A discloses a "high thermal conductivity polymer composite material and its preparation method," which uses a mixed filler of spherical aluminum nitride (AlN) and boron nitride (BN) to improve thermal conductivity through a melt blending process. In some scenarios, such thin polymer materials are required to take into account both mechanical and electrical properties, and even light transmittance. Therefore, the amount of filler added cannot be too high. For example, in thin films, the filler addition is usually around 30wt%. For example, in films and glues for optical applications, the filler addition is even less than 20wt%. For example, in high thermal conductivity gaskets and phase change films, the filler content is as high as 85wt%, resulting in significant deficiencies in strength and elasticity.
[0003] With the rapid development of the aforementioned fields, motors, circuit components and semiconductor devices are developing towards high voltage, high power, high integration, miniaturization, lightness and flexibility, which puts higher requirements on the performance of corresponding thin polymer-based composite materials such as films, thermal interface materials and coating materials. Traditional fillers need to be added in a very high amount to form a thermal conductive network and achieve a certain thermal conductivity, but the high addition amount leads to low strength, poor toughness, poor elasticity and opacity. Summary of the Invention
[0004] In order to solve the above-mentioned problem that traditional fillers require a high addition amount to form a thermal conductive network and achieve a certain thermal conductivity, but the high addition amount leads to low strength, poor toughness, poor elasticity, and opacity, the present invention is achieved through the following technical solutions.
[0005] In one aspect, the present invention provides a thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product, wherein the composite material comprises a polymer matrix and a one-dimensional aluminum nitride thermally conductive filler located in the polymer matrix;
[0006] The addition amount of the one-dimensional aluminum nitride thermal conductive filler is 0.1 to 90 wt% of the weight of the polymer matrix;
[0007] The thickness of the composite material is ≤3 mm, and the ratio of the average length of the one-dimensional aluminum nitride thermal conductive filler to the thickness of the composite material is 0.1 to 2.0;
[0008] The one-dimensional aluminum nitride thermal conductive fillers are randomly distributed in orientation, and some of the one-dimensional aluminum nitride fillers are connected alone or overlapped with each other to form a thermal conductive path running through the upper and lower surfaces of the composite material.
[0009] Preferably, the polymer matrix is selected from at least one of polyetheretherketone (PEEK), liquid crystal polymer (LCP), polyimide (PI), polyetherimide (PEI), polyamideimide (PAI), polyphenylene sulfone resin (PPSU), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyperfluoroethylene propylene (FEP), polyphenylene sulfide (PPS), polyethylene naphthalate (PEN), polydimethylsiloxane siloxane (PDMS), polyethylene terephthalate (PET), carbonate (PC), polypropylene (PP), silicone resin (SR), paraffin wax (PF), epoxy resin (ER), polyurethane (PU), etc.
[0010] Preferably, the one-dimensional aluminum nitride thermal conductive filler includes at least one of the following:
[0011] Aluminum nitride whiskers (AlN w ), in a single crystal state and one-dimensional morphology, with an average diameter of 0.1 to 20 μm and an average length of 10 to 1000 μm;
[0012] Aluminum nitride nanowires (AlN nw ), in a single-crystalline state and one-dimensional morphology, with an average diameter of 10 to 100 nm and an average length of 1 to 50 μm;
[0013] Aluminum nitride fiber (AlN f ), in a polycrystalline state and one-dimensional morphology, with an average diameter of 0.1 to 100 μm and an average length of 5 to 5000 μm.
[0014] AlN w 、AlN nw 、AlN f The modified product is formed by a coating or sintering process, and its form includes: a coaxial core-shell structure, a dendritic structure or a network structure.
[0015] Preferably, the one-dimensional aluminum nitride thermal conductive filler further comprises at least one of the following combinations:
[0016] A combination of one-dimensional aluminum nitride and spherical aluminum nitride or boron nitride (BN) in a weight ratio of 10:90 to 90:10;
[0017] A combination of one-dimensional aluminum nitride and lamellar graphene in a weight ratio of 20:80 to 60:40;
[0018] A combination of one-dimensional aluminum nitride and a liquid metal alloy, wherein the liquid metal is a gallium-indium-tin alloy with a weight ratio of 1:99-40:60;
[0019] Combination of one-dimensional aluminum nitride and one-dimensional aluminum nitride modifications.
[0020] Preferably, the one-dimensional aluminum nitride thermal conductive filler is surface modified, and the surface modifier is selected from at least one of silane coupling agents KH550, KH560, KH570, and titanate, and the added amount of the surface modifier is 0.1 to 3 wt% of the weight of the one-dimensional aluminum nitride thermal conductive filler.
[0021] Preferably, the composite material is in the form of a film, sheet, paste layer, adhesive layer, coating or paint layer, the thickness of the composite material is 10 to 3000 μm, and the thermal conductivity is ≥ 0.5 W·m -1 ·K -1 , thermal resistance ≤ 0.1℃·in 2 / W.
[0022] On the other hand, the present invention also provides a method for preparing a high thermal conductivity thin polymer-based composite material with a one-dimensional aluminum nitride filler, comprising the following steps:
[0023] S1: Surface modification of one-dimensional aluminum nitride filler;
[0024] S2: mixing the polymer matrix, the modified one-dimensional aluminum nitride thermal conductive filler and the additives, and forming a slurry, a paste or a molten mixture by melt mixing or solution dispersion;
[0025] S3: forming the slurry, paste or molten mixture into a raw film, raw sheet or coating by extrusion, casting or coating process;
[0026] S4: heat-treating or curing the raw film, raw sheet or coating to obtain a composite material.
[0027] Preferably, in S1:
[0028] The one-dimensional aluminum nitride thermal conductive filler is aluminum nitride whiskers, nanowires, fibers, and modified products thereof.
[0029] Preferably, in S2, the auxiliary agent includes:
[0030] The solvent is selected from at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP);
[0031] a curing agent selected from an amine curing agent or a platinum catalyst for epoxy resin;
[0032] an antioxidant selected from antioxidant 1010 or antioxidant 168;
[0033] Defoaming agent selected from silicone defoaming agent;
[0034] Or one or more of catalysts, accelerators, anti-settling agents, lubricants, plasticizers, anti-aging agents, stabilizers, defoamers, leveling agents, and adhesives.
[0035] Preferably, in S3:
[0036] After the extrusion process, it is subjected to biaxial stretching treatment, and the stretching temperature is the melting point of the polymer (T m ) below 30-50°C or glass transition temperature (T g ) above 50-100°C, and a stretching ratio of 2:1-5:1;
[0037] The curing temperature of the tape casting process is 200-350°C, and the drying stage adopts a step-by-step temperature increase;
[0038] The calendering process controls the thickness to 0.2 to 3 mm by the roller spacing;
[0039] The coating thickness of the coating process is controlled to 10 to 500 μm through spraying, scraping and dispensing parameters.
[0040] The present invention provides a thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified form, and a preparation method thereof. Compared with the existing technology, the present invention has the following advantages: by introducing one-dimensional aluminum nitride fillers and their modified form, the overall performance of the thin polymer-based composite material is significantly improved. The one-dimensional aluminum nitride filler, due to its single crystal or polycrystalline state, one-dimensional morphology, and large aspect ratio, forms a highly efficient thermal conductive network within the polymer matrix that runs through the upper and lower surfaces. Its one-dimensional structure can directly bridge the high-temperature and low-temperature sides of the composite material, forming an efficient heat conduction path, significantly reducing thermal resistance, achieving rapid heat conduction, and significantly improving the overall thermal conductivity of the material. At the same time, the strength, toughness, elasticity, and flexibility of the thin polymer-based composite material are significantly improved. In addition, the steric hindrance of its one-dimensional morphology has significant effects on preventing cracking, segregation, and oil seepage. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the distribution state of fillers and heat flow conduction in composite materials.
[0042] Figure 2 This is the SEM image of aluminum nitride whiskers.
[0043] Figure 3 This is the SEM image of aluminum nitride nanowires.
[0044] Figure 4 This is the SEM image of aluminum nitride fiber.
[0045] Figure 5 This is the SEM image of the polyetheretherketone composite film with one-dimensional aluminum nitride whisker filler.
[0046] Figure 6 This is the SEM photo of the liquid crystal polymer composite film with one-dimensional aluminum nitride whisker filler.
[0047] Figure 7 This is the SEM photo of the polyimide composite film with one-dimensional aluminum nitride whisker filler.
[0048] Figure 8 This is an SEM photo of a thermally conductive silicone gasket with one-dimensional aluminum nitride whisker filler.
[0049] Figure 9 This is an SEM photo of a thermally conductive phase change sheet with one-dimensional aluminum nitride whisker filler.
[0050] Figure 10 This is an SEM photo of liquid metal composite thermal paste with one-dimensional aluminum nitride nanowire filler.
[0051] Figure 11 This is the SEM photo of the thermal conductive epoxy resin coating layer with one-dimensional aluminum nitride fiber filler.
[0052] Figure 12 This is an SEM photo of a thermally conductive organic silicone layer with one-dimensional aluminum nitride nanowire filler.
[0053] Figure 13 This is an SEM photo of a thermally conductive polyimide paint layer with one-dimensional aluminum nitride whisker filler. DETAILED DESCRIPTION
[0054] The present invention is further described below with reference to specific examples. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of protection of the present invention.
[0055] The following describes the embodiments of the present invention through specific examples. Those skilled in the art will readily understand the other advantages and benefits of the present invention from the disclosure herein. The present invention may also be implemented or applied through various other specific embodiments, and the details in this specification may be modified or altered based on different viewpoints and applications without departing from the spirit of the present invention.
[0056] A thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product and a preparation method thereof, by using one-dimensional aluminum nitride whiskers (AlN whisker, AlN w ), aluminum nitride nanowire (AlN nanowire, AlN nw ), aluminum nitride fiber (AlN fiber, AlN f ) fillers to achieve high thermal conductivity of films, sheets, paste layers, adhesive layers, membrane layers, coatings, and paint layers of polymer-based composite materials such as polyetheretherketone (PEEK), liquid crystal polymer (LCP), polyimide (PI), polyetherimide (PEI), polyamideimide (PAI), polyphenylene sulfone resin (PPSU), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyfluoroethylene propylene (FEP), polyphenylene sulfide (PPS), polyethylene naphthalate (PEN), polydimethylsiloxane (PDMS), polyethylene terephthalate (PET), carbonate (PC), polypropylene (PP), silicone resin (SR), paraffin (PF), epoxy resin (ER), polyurethane (PU), etc., which are suitable for scenarios requiring thermal management in fields such as electric vehicles, wind power generation, high-speed railways, aerospace, 5G communications, mobile phones, microelectronics, and semiconductor devices.
[0057] The thin type refers to that the dimension of the thickness direction of the composite material is much smaller than the dimension of the surface direction, and the thickness is usually 3 mm or less, especially the thickness is 1 mm or less, and especially 100 μm or less. The form with relatively large plane size includes: independent films, thermal interface materials filled in the gap (thermal gaskets, thermal phase change sheets, thermal gels, thermal pastes, thermal glue, etc.), and thermal coatings (paint layers, film layers) attached to the surface of the substrate.
[0058] The thermal conductivity refers to the fact that the thin composite material has the function of conducting heat and dissipating heat, that is, conducting heat from the side with a higher temperature to the side with a lower temperature.
[0059] The filler refers to the material filled in the polymer composite matrix, which has the function of improving the thermal conductivity, mechanical properties, electrical insulation properties, stability, etc. of the composite material.
[0060] Modified materials of one-dimensional aluminum nitride (AlN) refer to coaxial core-shell structures, dendritic structures, network structures, etc. formed by coating and sintering one-dimensional aluminum nitride (AlN) with other materials.
[0061] Compared with other fillers, the thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product is prepared by one-dimensional AlN (AlN w 、AlN nw 、AlN f or its modified products and their compositions), or its combination fillers with other fillers, to obtain thin polymer-based composite materials with different microstructures. Due to its one-dimensional morphology and large aspect ratio, one-dimensional AlN (AlN w 、AlN nw 、AlN f (or its modified products and combinations thereof) can form a highly efficient thermal conductive network at relatively low addition levels, significantly improving the thermal conductivity and significantly reducing the thermal resistance of thin polymer-based composites while maintaining high insulation and light transmittance, and significantly enhancing their strength, toughness, and flexibility. Furthermore, the steric hindrance effect of the one-dimensional AlN improves stability, prevents cracking and segregation, and inhibits oil seepage. Specifically, by regulating the length of the one-dimensional AlN material so that its average length approximates the thickness of the thin polymer-based composite, a direct bridge between the high-temperature side and the low-temperature side is created, forming a high-speed thermal conduction pathway. Heat is then transferred directly from the high-temperature side to the low-temperature side through the one-dimensional AlN, significantly reducing the thermal resistance between the thermally conductive fillers and between the fillers and the matrix, thereby significantly improving the thermal conductivity of the thin polymer-based composite.
[0062] Furthermore, when a combination of one-dimensional AlN filler and other fillers is used, the one-dimensional AlN filler can bridge the other fillers together to form an interwoven and interlocking microstructure in the polymer matrix, thereby forming an efficient thermal conductive network at a lower addition amount of one-dimensional AlN filler. At the same time, the presence of one-dimensional AlN filler also significantly improves the thermal conductivity of thin polymer-based composite materials, significantly reduces their thermal resistance, while maintaining high insulation properties, and significantly improves their strength, toughness, flexibility and stability.
[0063] The following describes a thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product and a preparation method thereof through specific embodiments of the present application.
[0064] Example 1: Reference Figure 1 、 Figure 2 、 Figure 3 and Figure 4 , a thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product, the composite material consisting of a polymer matrix and a one-dimensional aluminum nitride thermal conductive filler located in the polymer matrix and a combination thereof with other fillers;
[0065] The one-dimensional aluminum nitride thermal conductive filler is added in an amount of 30 wt% of the weight of the polymer-based composite material;
[0066] The thickness of the composite material is ≤3 mm, and the ratio of the length of the one-dimensional aluminum nitride thermal conductive filler to the thickness of the composite material is 2.0;
[0067] The one-dimensional aluminum nitride thermal conductive filler forms a thermal conductive path penetrating the upper and lower surfaces of the composite material along the thickness direction of the composite material.
[0068] The polymer matrix is selected from at least one of polyetheretherketone (PEEK), liquid crystal polymer (LCP), polyimide (PI), polyetherimide (PEI), polyamideimide (PAI), polyphenylene sulfone resin (PPSU), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyperfluoroethylene propylene (FEP), polyphenylene sulfide (PPS), polyethylene naphthalate (PEN), polydimethylsiloxane siloxane (PDMS), polyethylene terephthalate (PET), polycarbonate (PC), and polypropylene (PP).
[0069] One-dimensional aluminum nitride thermal conductive fillers include: aluminum nitride whiskers (AlN w ), in a single crystal state and one-dimensional morphology, with an average diameter of 1 μm and an average length of 40 μm.
[0070] The one-dimensional aluminum nitride thermal conductive filler further includes: a combination of one-dimensional aluminum nitride and flake boron nitride (BN), spherical aluminum nitride (AlN) or spherical aluminum oxide (Al2O3), with a weight ratio of 20:80;
[0071] The one-dimensional aluminum nitride thermal conductive filler is subjected to surface modification treatment, and the surface modifier is silane coupling agent KH550, and the addition amount of the surface modifier is 0.1wt% of the weight of the one-dimensional aluminum nitride thermal conductive filler.
[0072] The composite material is in the form of a thin film, the thickness of the composite material is 20 μm, and the thermal conductivity is ≥1.0 W·m -1 ·K -1 .
[0073] Example 2: This example differs from Example 1 in that:
[0074] The addition amount of the one-dimensional aluminum nitride thermal conductive filler is 80 wt % of the weight of the composite material.
[0075] The thickness of the composite material is less than or equal to 3 mm, and the ratio of the length of the one-dimensional aluminum nitride thermal conductive filler to the thickness of the composite material is 0.5.
[0076] The polymer matrix is selected from at least one of silicone resin (SR) and paraffin (PF). One-dimensional aluminum nitride thermal conductive filler includes: aluminum nitride whiskers (AlN w ) or its modified product with coaxial core-shell structure, dendritic structure or network structure formed by coating or sintering process, wherein AlN w It is in a single crystal state and one-dimensional morphology, with an average diameter of 10μm and an average length of 100μm.
[0077] The one-dimensional aluminum nitride thermal conductive filler also includes: a combination of one-dimensional aluminum nitride, lamellar graphene filler, and spherical metal aluminum powder, with a weight ratio of 40:60;
[0078] The one-dimensional aluminum nitride thermal conductive filler is subjected to surface modification treatment, the surface modifier is selected from silane coupling agent KH560, and the added amount of the surface modifier is 3wt% of the weight of the one-dimensional aluminum nitride thermal conductive filler.
[0079] The composite material is in the form of a sheet, and the thickness of the composite material is 200 μm.
[0080] Example 3: This example differs from Example 1 in that:
[0081] The added amount of the one-dimensional aluminum nitride thermal conductive filler is 0.4 wt % of the weight of the polymer-based composite material.
[0082] The thickness of the composite material is less than or equal to 3 mm, and the ratio of the length of the one-dimensional aluminum nitride thermal conductive filler to the thickness of the composite material is 1.0.
[0083] The polymer matrix is selected from at least one of silicone resins (SR).
[0084] One-dimensional aluminum nitride thermal conductive fillers include: aluminum nitride nanowires (AlNnw ), in a single crystal state and one-dimensional morphology, with an average diameter of 0.1 μm and an average length of 50 μm.
[0085] The one-dimensional aluminum nitride thermal conductive filler further comprises at least one of the following combinations: a combination of one-dimensional aluminum nitride and a liquid metal alloy, wherein the liquid metal is a gallium indium tin alloy, and the weight ratio is 0.5:100;
[0086] The one-dimensional aluminum nitride thermal conductive filler is subjected to surface modification treatment, the surface modifier is selected from silane coupling agent KH570, and the added amount of the surface modifier is 2wt% of the weight of the one-dimensional aluminum nitride thermal conductive filler.
[0087] The composite material is in the form of a paste, and the thickness of the composite material is 50 μm.
[0088] Example 4: This example differs from Example 1 in that:
[0089] The added amount of the one-dimensional aluminum nitride thermal conductive filler is 50 wt % of the weight of the polymer-based composite material.
[0090] The thickness of the composite material is less than or equal to 3 mm, and the ratio of the length of the one-dimensional aluminum nitride thermal conductive filler to the thickness of the composite material is 0.2.
[0091] The polymer matrix is selected from at least one of silicone resin (SR), epoxy resin (ER), polyurethane (PU), and polyimide (PI).
[0092] One-dimensional aluminum nitride thermal conductive fillers include: aluminum nitride fiber (AlN f ), in a polycrystalline state and one-dimensional morphology, with an average diameter of 5 μm and an average length of 100 μm.
[0093] The one-dimensional aluminum nitride thermal conductive filler is subjected to surface modification treatment, the surface modifier is selected from silane coupling agent KH570, and the added amount of the surface modifier is 2wt% of the weight of the one-dimensional aluminum nitride thermal conductive filler.
[0094] The composite material is in the form of a glue layer, a coating layer or a paint layer, and the thickness of the composite material is 500 μm.
[0095] Example 5: A method for preparing a thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product, comprising the following steps:
[0096] S1: Surface modification of one-dimensional aluminum nitride filler;
[0097] S2: mixing the polymer matrix, the modified one-dimensional aluminum nitride thermal conductive filler, and the additive to form a molten mixture by melt mixing;
[0098] S3: forming the molten mixture into a raw film by extrusion and casting process;
[0099] S4: heat-treating the raw material film, curing it or maintaining the paste layer to obtain a composite material.
[0100] In S1, the one-dimensional aluminum nitride thermal conductive filler is aluminum nitride whiskers, nanowires or fibers.
[0101] In S2, the additives include:
[0102] A lubricant selected from one of magnesium stearate and oleamide;
[0103] an antioxidant selected from diphenylamine;
[0104] Plasticizer selected from dioctyl phthalate;
[0105] Or one or more of anti-settling agents, anti-aging agents, and stabilizers.
[0106] In S3:
[0107] After the extrusion casting process, it is subjected to biaxial stretching treatment, and the stretching temperature is the melting point of the polymer (T m ) below 30℃ or glass transition temperature (T g ) above 50°C, the stretching ratio is 2:1;
[0108] Example 6: The difference between this example and Example 5 is that:
[0109] In S2, the additives include:
[0110] A solvent selected from N,N-dimethylacetamide (DMAc) and N,N-dimethylformamide (DMF);
[0111] Or one or more of anti-settling agent, lubricant, plasticizer, anti-aging agent, stabilizer, defoaming agent, leveling agent.
[0112] In S3:
[0113] The slurry is then subjected to biaxial stretching after the casting process, and the stretching temperature is the melting point of the polymer (T m ) below 50℃ or glass transition temperature (T g ) above 100°C, the stretching ratio is 5:1;
[0114] The drying stage after the casting process adopts a step-by-step temperature increase, and the curing temperature is 300°C;
[0115] The coating thickness of the coating process was controlled to 500 μm by doctor blade, spray or dip coating parameters.
[0116] Embodiment 7: This embodiment differs from Embodiment 5 in that:
[0117] In S2, the additives include:
[0118] diluent selected from methyl silicone oil;
[0119] The catalyst is selected from vinyl-coordinated platinum catalyst and chloroplatinic acid;
[0120] an inhibitor selected from the group consisting of acetylenic alcohols;
[0121] The anti-aging agent is selected from β-cyclodextrin;
[0122] Or one or more of anti-settling agents, plasticizers, and binders.
[0123] In S3:
[0124] The calendering process was selected with a roller spacing of 200 μm.
[0125] Example 8: Reference Figure 5 , a thermally conductive PEEK composite film containing one-dimensional AlN filler was prepared by combining extrusion casting method with stretching process.
[0126] First, silane coupling agent KH570 was used to w , AlN powder for surface modification, KH550 for surface modification of BN, and then dried at 120℃ for 4h; weigh AlN according to weight ratio w :AlN powder is 1:1 and mixed to form a thermal conductive filler containing one-dimensional AlN;
[0127] 60 parts of thermal conductive filler containing one-dimensional AlN, 100 parts of PEEK powder, and 1 part of lubricant magnesium stearate were weighed respectively according to weight ratio;
[0128] All raw materials were dried at 80 to 120 °C for 6 h;
[0129] The thermal conductive filler containing one-dimensional AlN, PEEK powder, and magnesium stearate are premixed in a high-speed mixer for 30 minutes to obtain a premix;
[0130] The premix is melted, extruded, cooled, and pelletized at 380°C through a twin-screw extruder to obtain composite pellets.
[0131] The composite pellets are melted at 380°C through a single-screw extruder, extruded through a T-shaped die at 360°C, cast into a film through a casting machine, and then biaxially stretched at 340°C (longitudinal / transverse stretching ratio ≥ 3:1) through a traction stretching roller. Finally, after cooling to a cooling roller below 30°C, the film is cut and wound to produce a thermally conductive PEEK composite film containing one-dimensional AlN filler.
[0132] The thermally conductive PEEK film has a thickness of 12 μm and a thermal conductivity of 1.7 W·m -1 ·K -1, compressive strength 194V / μm, tensile strength 117MPa, and elongation at break 18%.
[0133] Example 9: Reference Figure 6 , melt extrusion combined with blown film forming process was used to prepare thermal conductive liquid crystal polymer LCP composite film containing one-dimensional AlN filler.
[0134] First, silane coupling agent KH570 was used to w Surface modification was performed by using titanate to modify the surface of spherical AlN and AlN powder, and then drying at 120 °C for 4 h;
[0135] Weigh AlN according to weight ratio w : spherical AlN:AlN powder is 1:1:1 and mixed to form a thermal conductive filler containing one-dimensional AlN;
[0136] Weigh 80 parts of a thermally conductive filler containing one-dimensional AlN, 100 parts of a liquid crystal polymer, 0.1 parts of a lubricant oleamide, 0.3 parts of a calcium-zinc composite stabilizer, 0.2 parts of an antioxidant diphenylamine, and 0.5 parts of a plasticizer dioctyl phthalate according to weight proportion;
[0137] All raw materials were dried at 80°C to 120°C for 6 h;
[0138] The thermal conductive filler containing one-dimensional AlN, liquid crystal polymer, oleamide, calcium zinc composite stabilizer, diphenylamine, and dioctyl phthalate are added to a single-screw extruder, and when the set temperature reaches 300° C. (the melting point of LCP is 280° C.), melt-stirred and mixed;
[0139] A film bubble was formed by extrusion through an O-type die, and a gas medium was introduced into the film bubble to inflate the film bubble to obtain a cylindrical film bubble (blowing ratio 6, stretching ratio 4). The film was then annealed at 270°C for 30 minutes, and finally cooled to room temperature at a cooling rate of 2°C / min under nitrogen protection to set the shape. The film was then pulled out and rolled into shape by a traction roller to obtain a thermally conductive LCP composite film containing one-dimensional AlN filler.
[0140] The thermally conductive LCP film has a thickness of 20 μm and a thermal conductivity of 2.4 W·m -1 ·K -1 , compressive strength 217V / μm, tensile strength 102MPa, and elongation at break 13.7%.
[0141] Example 10: Reference Figure 7 , a thermally conductive polyimide composite film containing one-dimensional AlN filler was prepared by solution casting method combined with stretching process.
[0142] First, silane coupling agent KH570 was used to w, AlN powder was surface modified, and the flake BN was surface modified with KH550, and then dried at 120 °C for 4 h;
[0143] Weigh AlN according to weight ratio w :BN particles are 1:2 and mixed to form a thermal conductive filler containing one-dimensional AlN;
[0144] Weigh 30 parts of a thermally conductive filler containing one-dimensional AlN, 160 parts of N,N'-dimethylacetamide (DMAc), 18.5 parts of 4,4'-diaminodiphenyl ether (ODA), and 20 parts of pyromellitic dianhydride (PMDA) powder;
[0145] All raw materials were dried at 80°C to 120°C for 6 h;
[0146] The thermal conductive filler containing one-dimensional AlN is added to the N,N'-dimethylacetamide (DMAc), dispersed in a high-speed disperser at 1200 rpm for 30 minutes, and then the 4,4'-diaminodiphenyl ether (ODA) is added and stirred evenly;
[0147] Then, the pyromellitic dianhydride (PMDA) powder was added in batches under stirring, and the mixture was stirred in a high-speed disperser at 600 rpm for 30 minutes while controlling the temperature at 0-25°C to obtain a slurry;
[0148] Subsequently, the slurry was degassed under vacuum stirring at -0.09 MPa for 30 minutes to form a slurry. The slurry was evenly coated on a metal belt or release film by a scraper of a tape casting machine at a coating speed of 5 m / min to form a wet film with a thickness of 120 μm.
[0149] Low-temperature drying at 80-120°C removes most of the solvent to form a green film. Subsequently, the green film is heated stepwise to 300°C under nitrogen protection for 2 hours to dehydrate and cyclize PAA to form a polyimide film. The film is then biaxially stretched (longitudinal / transverse stretching ratio ≥ 3:1) by traction stretching rollers, cooled and shaped, and wound to produce a thermally conductive PI composite film containing one-dimensional AlN filler.
[0150] The thermally conductive PI film has a thickness of 10 μm and a thermal conductivity of 2.1 W·m -1 ·K -1 , compressive strength 184V / μm, tensile strength 97MPa, elongation at break 10.5%.
[0151] Example 11: Reference Figure 8 , a thermal conductive silicone gasket containing one-dimensional AlN filler was prepared by calendering method.
[0152] First, silane coupling agent KH560 was used to w, spherical AlN was surface modified, and flake BN was surface modified with KH550 and dried at 120 °C for 4 h;
[0153] Weigh AlN according to weight ratio w : flake BN: spherical AlN are mixed in a ratio of 1:1:1 to form a thermally conductive filler containing one-dimensional AlN; 850 parts of the thermally conductive filler containing one-dimensional AlN, 100 parts of vinyl silicone oil (vinyl content of 0.3% by weight, viscosity of 2000 mPa·s), 2 parts of hydrogenated silicone oil (hydrogen content of 0.3% by weight), 0.2 parts of an acetylene alcohol inhibitor, 0.2 parts of a vinyl-coordinated platinum catalyst, and 2 parts of an antioxidant, β-cyclodextrin, are weighed;
[0154] All raw materials are dried at 80° C. to 120° C. for 6 hours; the thermal conductive filler containing one-dimensional AlN, vinyl silicone oil, hydrogenated silicone oil, inhibitor, and anti-aging agent in the above-mentioned weight portions are placed in an internal mixer and kneaded at RT to 60° C. for 30 to 60 minutes; then the above-mentioned weight portions of catalyst are added and kneaded at RT to 60° C. for 30 minutes to obtain a thermal conductive silicone rubber compound;
[0155] The thermally conductive silicone material is rolled into a sheet with a thickness of 0.2 mm in a calender, and then vulcanized in a vulcanizer at a temperature of 130° C. for 2 hours. After cutting, a thermally conductive silicone gasket containing one-dimensional AlN filler is obtained.
[0156] The thermal pad has a thickness of 0.2 mm and a thermal conductivity of 10 W·m -1 ·K -1 , tensile strength 3.6MPa, elongation at break 30%, rebound rate 30%, Shore hardness 75.
[0157] Example 12: Reference Figure 9 , a thermal conductive phase change sheet containing one-dimensional AlN filler was prepared by calendering method.
[0158] First, silane coupling agent KH560 was used to w and Al powder filler for surface modification, and weigh AlN at a weight ratio of 1:4 w :Al powder, and mixed to form a thermal conductive filler containing one-dimensional AlN;
[0159] Weigh 100 parts of a thermally conductive filler containing one-dimensional AlN, 10 parts of paraffin powder (40-70° C.) as a phase change material, 10 parts of an organic silicone resin, and 0.5 parts of an antioxidant, di-tert-butylphenol phosphate, according to weight ratio;
[0160] All raw materials were dried at 80°C to 120°C for 6 h;
[0161] The thermal conductive filler containing one-dimensional AlN, paraffin, silicone resin, di-tert-butylphenol phosphate, and polyethylene are melt-mixed in a vacuum kneader at 70° C. to form a semi-molten mass with good plasticity;
[0162] The material dough is placed on a feed plate preheated to 70-80° C., rolled to a thickness of 0.2 mm by a rolling roller preheated to 70-80° C., and cooled to form a thermal conductive phase change sheet containing one-dimensional AlN filler.
[0163] The thermal conductive phase change sheet has a thickness of 0.2 mm and a thermal conductivity of 10.8 W·m -1 ·K -1 , oil permeability 0.04%, thermal resistance 0.011℃·in 2 / W.
[0164] Example 13: Reference Figure 10 A liquid metal composite thermal conductive paste containing one-dimensional AlN filler is prepared by a stirring dispersion method, and a liquid metal composite thermal conductive paste layer containing one-dimensional AlN filler is formed by a blade coating and compacting method.
[0165] First, silane coupling agent KH570 was used to nw Surface modification was performed to serve as a filler containing one-dimensional AlN;
[0166] Weigh 2 parts of a filler containing one-dimensional AlN, 100 parts of a gallium-indium-tin alloy liquid metal, 5 parts of expanded graphite, 10 parts of methyl silicone oil (viscosity of 1000 mPa·s), and 2 parts of an antioxidant, gallium picolinate, according to weight ratio;
[0167] All raw materials were dried at 80° C. to 120° C. for 6 hours. The filler containing one-dimensional AlN, gallium-indium-tin alloy, expanded graphite, methyl silicone oil, and gallium pyridinedicarboxylate were added to a high-speed disperser and stirred at 800 rpm for 30 minutes under vacuum to prepare a liquid metal composite thermal conductive paste containing one-dimensional AlN filler.
[0168] In actual use, liquid metal composite thermal conductive paste containing one-dimensional AlN filler is scraped on the surface of devices such as chips, and then the heat sink is pressed tightly. A liquid metal composite thermal conductive paste layer containing one-dimensional AlN filler is formed between the gap between the device and the heat sink.
[0169] The liquid metal composite thermal paste containing one-dimensional AlN filler has a thickness of 30 μm and a thermal conductivity of 11.8 W·m -1 ·K -1 , thermal resistance 0.0071℃·in 2 / W, more than 2000 times of hot and cold shock from -40℃ to 125℃, no gold precipitation, no cracking, no sagging.
[0170] Example 14: Reference Figure 11 A thermal conductive epoxy resin coating containing one-dimensional AlN filler is prepared by a stirring dispersion method, and a thermal conductive epoxy resin coating containing one-dimensional AlN filler is formed by a brush coating method.
[0171] Firstly, silane coupling agent KH560 was used to f Surface modification with AlN powder;
[0172] Weigh the modified AlN in a weight ratio of 1:1 f and AlN powder and mixed to form a thermal conductive filler containing one-dimensional AlN;
[0173] Weigh 50 parts of a thermally conductive filler containing one-dimensional AlN, 100 parts of an epoxy resin, 2 parts of a 2-methylimidazole curing agent, 2 parts of a substituted urea accelerator, 0.5 parts of an organosilicon leveling agent, 1 part of an organosilicon defoaming agent, and 0.5 parts of a phenolic antioxidant according to weight ratio; dry all the raw materials at 80° C. to 120° C. for 6 hours;
[0174] The thermal conductive filler containing one-dimensional AlN, epoxy resin, 2-methylimidazole curing agent, substituted urea accelerator, silicone leveling agent, silicone defoaming agent, and phenolic antioxidant are heated, stirred, mixed, and vacuum degassed in a homogenizer to form a thermal conductive epoxy resin coating containing one-dimensional AlN filler.
[0175] In actual use, it is applied on the surface of the component by brushing and then cured at room temperature to form a thermally conductive epoxy resin coating containing one-dimensional AlN filler.
[0176] The thermally conductive epoxy resin coating containing one-dimensional AlN filler has a thickness of 100 μm and a thermal conductivity of 2.3 W·m -1 ·K -1 , voltage resistance 182V / μm.
[0177] Example 15: Reference Figure 12 The thermal conductive organic silicone water containing one-dimensional AlN filler is prepared by a stirring dispersion method, and the thermal conductive organic silicone layer containing one-dimensional AlN filler is formed by a dispensing method and a coating method.
[0178] First, silane coupling agent KH560 was used to nw Performing surface modification to form a thermally conductive filler containing one-dimensional AlN;
[0179] Weigh 15 parts of a thermally conductive filler containing one-dimensional AlN, 100 parts of a modified silicone resin, 10 parts of a silicone oil diluent, and 10 parts of an amine curing agent according to weight proportion;
[0180] All raw materials were dried at 80 to 120 ° C for 6 h;
[0181] The thermal conductive filler containing one-dimensional AlN, modified organic silicone resin, silicone oil diluent, and amine curing agent are stirred and dispersed at 1000 rpm in a high-speed disperser in vacuum for 60 minutes to prepare a thermal conductive organic silicone water containing one-dimensional AlN filler.
[0182] In actual use, the thermally conductive organic silicone water is applied on the ultraviolet LED chip, or coated on the surface of the component, and vulcanized at 130°C for 2 hours to form a thermally conductive organic silicone coating containing one-dimensional AlN filler.
[0183] The thermally conductive silicone coating containing one-dimensional AlN filler has a thickness of 500 μm and a thermal conductivity of 1.3 W·m -1 ·K -1 , light transmittance 90%, long-term use, no obvious fogging phenomenon, light transmittance attenuation is less than 1%.
[0184] Example 16: Reference Figure 13 A thermally conductive polyimide paint containing one-dimensional AlN filler is prepared by a stirring dispersion method, and a thermally conductive polyimide paint layer containing one-dimensional AlN filler is formed by a dip coating method.
[0185] First, silane coupling agent KH570 was used to w Surface modification: Silane coupling agent KH550 is used to modify the surface of Al2O3 powder particles;
[0186] Weigh AlN in a weight ratio of 1:2 w and Al2O3 powder, and mixed to form a thermal conductive filler containing one-dimensional AlN; weighing 9 parts of the thermal conductive filler containing one-dimensional AlN, 10 parts of 3,3',4,4',-biphenyltetracarboxylic dianhydride (BPDA) powder, 150 parts of N,N-dimethylacetamide, and 18 parts of p-phenylenediamine (PPD) according to weight ratio;
[0187] All raw materials were dried at 80 to 120 ° C for 6 h;
[0188] The thermal conductive filler containing one-dimensional AlN and 3,3',4,4',-biphenyltetracarboxylic dianhydride (BPDA) powder were dissolved in N,N-dimethylacetamide and p-phenylenediamine (PPD) in a protective atmosphere and stirred evenly; then the thermal conductive filler containing one-dimensional AlN was added thereto and dispersed in a high-speed disperser at 1000 rpm for 30 minutes;
[0189] Then, the p-phenylenediamine (PPD) was added thereto, and the mixture was stirred at 300 rpm and 80° C. for 10 h in a nitrogen atmosphere, and then cooled to room temperature to prepare a thermal conductive polyimide paint containing one-dimensional AlN filler.
[0190] In actual use, the thermal conductive paint is injected into the container of a coating device such as a pulling coating machine, the copper wire is immersed in it for coating, and then the coating is pulled at a speed of 30 mm / min. Subsequently, it is dried at 80°C, 100°C, and 120°C for 1 hour respectively, and then heat-treated at 150°C, 200°C, 250°C, and 300°C for 40 minutes respectively, to form a thermal conductive polyimide paint layer containing one-dimensional AlN filler on the surface of the copper wire.
[0191] The thermally conductive polyimide paint containing one-dimensional AlN filler has a paint layer thickness of 12 μm and a thermal conductivity of 1.5 W·m -1 ·K -1 , voltage resistance 230V / μm, no falling off or delamination occurs during long-term use at 300℃.
[0192] In summary, compared with the existing technology, it has the following beneficial effects:
[0193] By introducing one-dimensional aluminum nitride (AlN) fillers and their modifications, the overall performance of thin polymer-based composites is significantly improved. Leveraging their single-crystal or polycrystalline one-dimensional morphology and large aspect ratio, one-dimensional AlN fillers form a highly efficient thermally conductive network within the polymer matrix, extending across the upper and lower surfaces. Their one-dimensional structure directly bridges the high-temperature and low-temperature sides of the composite, forming an efficient heat conduction path. This significantly reduces thermal resistance, enables rapid heat conduction, and significantly enhances the material's overall thermal conductivity. Simultaneously, the strength, toughness, elasticity, and flexibility of thin polymer-based composites are significantly enhanced. Furthermore, the steric hindrance effect of one-dimensional AlN enhances the structural stability of the material, effectively suppressing cracking, segregation, and oil seepage in thin polymer-based composites. Consequently, thermally conductive thin polymer-based composites containing one-dimensional AlN and its modifications maintain excellent, stable, reliable, and durable performance even in complex and harsh environments.
[0194] Composite materials can achieve a thin structure with dimensions in the thickness direction much smaller than those in the surface direction. By adjusting the length of the one-dimensional aluminum nitride filler to match the material thickness, a particularly efficient heat conduction path can still be formed in an ultra-thin form, solving the problems of poor mechanical properties and low thermal conductivity caused by the thinning of traditional materials, and meeting the lightweight and compact design requirements of electronic devices.
[0195] The preparation process covers various molding methods such as extrusion, casting, calendering, and coating. It can flexibly prepare products in different forms such as films, sheets, paste layers, coatings, etc., which are adapted to the thermal management needs of electric vehicles, 5G communications, semiconductor devices and other fields. It is especially suitable for scenarios with strict requirements on insulation, light transmittance, and temperature resistance.
[0196] One-dimensional aluminum nitride can be combined with spherical fillers, lamellar fillers, and liquid metals to form a synergistic thermal conductivity system. Through the "one-dimensional skeleton + multi-component filler" model, a three-dimensional thermal conductivity network is constructed, reducing the amount of single filler while further improving thermal conductivity efficiency and material adaptability, meeting the diverse requirements of thermal conductivity, strength, toughness, flexibility, and stability in different scenarios.
[0197] Surface modification technology improves filler dispersion efficiency and reduces additive usage; high thermal conductivity can be achieved with low filler additions, reducing material costs and environmental impact. The simple process is suitable for industrial production and provides a new path for greener and more cost-effective high-thermal conductivity composite materials.
[0198] Thus, although the invention has been described herein with reference to specific embodiments thereof, freedom of modification, various changes and substitutions are contemplated within the foregoing disclosure, and it should be understood that in some cases, some features of the invention will be employed without the corresponding use of other features without departing from the scope and spirit of the claimed invention. Thus, many modifications may be made to adapt a particular environment or material to the true scope and spirit of the invention. The invention is not intended to be limited to the specific terminology used in the claims below and / or to the specific embodiments disclosed as the best mode contemplated for carrying out the invention, but the invention is intended to include any and all embodiments and equivalents falling within the scope of the appended claims. Thus, the scope of the invention will be determined solely by the appended claims.
Claims
1. A thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product, characterized in that: The composite material consists of a polymer matrix and a one-dimensional aluminum nitride thermal conductive filler located in the polymer matrix; The addition amount of the one-dimensional aluminum nitride thermal conductive filler is 0.1 to 90 wt% of the weight of the polymer matrix; The thickness of the composite material is ≤3 mm, and the ratio of the average length of the one-dimensional aluminum nitride thermal conductive filler to the thickness of the composite material is 0.1 to 2.0; A portion of the one-dimensional aluminum nitride thermal conductive fillers are connected individually or overlapped with each other to form a thermal conductive path running through the upper and lower surfaces of the composite material.
2. The composite material according to claim 1, characterized in that The polymer matrix is selected from at least one of polyetheretherketone (PEEK), liquid crystal polymer (LCP), polyimide (PI), polyetherimide (PEI), polyamideimide (PAI), polyphenylene sulfone resin (PPSU), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyperfluoroethylene propylene (FEP), polyphenylene sulfide (PPS), polyethylene naphthalate (PEN), polydimethylsiloxane siloxane (PDMS), polyethylene terephthalate (PET), carbonate (PC), polypropylene (PP), silicone resin (SR), paraffin wax (PF), epoxy resin (ER), and polyurethane (PU).
3. The composite material according to claim 1, characterized in that The one-dimensional aluminum nitride thermal conductive filler includes at least one of the following: Aluminum nitride whiskers (AlN w ), in a single crystal state and one-dimensional morphology, with an average diameter of 0.1 to 20 μm and an average length of 10 to 1000 μm; Aluminum nitride nanowires (AlN nw ), in a single-crystalline state and one-dimensional morphology, with an average diameter of 10 to 100 nm and an average length of 1 to 50 μm; Aluminum nitride fiber (AlN f ), in a polycrystalline state and one-dimensional morphology, with an average diameter of 0.1 to 100 μm and an average length of 5 to 5000 μm. One-dimensional aluminum nitride also includes AlN w 、AlN nw 、AlN f The modified product is formed by a coating or sintering process, and its form includes: a coaxial core-shell structure, a dendritic structure or a network structure.
4. The composite material according to claim 3, characterized in that The one-dimensional aluminum nitride thermal conductive filler further comprises at least one of the following combinations: A combination of one-dimensional aluminum nitride with spherical aluminum nitride, boron nitride (BN), and aluminum oxide (Al2O3) in a weight ratio of 5:95-95:5; A combination of one-dimensional aluminum nitride, lamellar boron nitride, and graphene in a weight ratio of 5:95 to 95:5; A combination of one-dimensional aluminum nitride, liquid gallium indium tin alloy, and spherical aluminum powder in a weight ratio of 0.2:99.8-40:60; Combination of one-dimensional aluminum nitride and one-dimensional aluminum nitride modifications.
5. The composite material according to claim 1, characterized in that The one-dimensional aluminum nitride thermal conductive filler is surface modified, and the surface modifier is selected from at least one of silane coupling agents KH550, KH560, KH570, and titanate, and the added amount of the surface modifier is 0.1-3wt% of the weight of the one-dimensional aluminum nitride thermal conductive filler.
6. The composite material according to claim 1, characterized in that The composite material is in the form of a film, sheet, paste layer, adhesive layer, coating or paint layer, the thickness of the composite material is 10 to 3000 μm, and the thermal conductivity is ≥0.5 W·m -1 ·K -1 , thermal resistance ≤ 0.1℃·in 2 / W.
7. The method for preparing a thermally conductive thin polymer-based composite material containing one-dimensional aluminum nitride and its modified product according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Surface modification of one-dimensional aluminum nitride filler; S2: mixing the polymer matrix, the modified one-dimensional aluminum nitride thermal conductive filler and the additive, and forming a molten mixture, slurry or paste by melt mixing or solution dispersion; S3: forming the molten mixture, slurry or paste into a raw film, raw sheet or coating by extrusion, casting, calendaring or coating process; S4: heat-treating, curing or maintaining the raw film, raw sheet or coating in a paste-like state to obtain a composite material.
8. The preparation method according to claim 7, characterized in that In S1: The one-dimensional aluminum nitride thermal conductive filler is aluminum nitride whiskers, nanowires, fibers, modified products thereof, or a mixture thereof.
9. The preparation method according to claim 7, characterized in that In S2, the additives include: The solvent is selected from at least one of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), and N-methylpyrrolidone (NMP); A diluent selected from at least one of methyl silicone oil, ethyl silicone oil, and ethanol; a curing agent selected from an amine curing agent or a platinum catalyst for epoxy resin; an antioxidant selected from antioxidant 1010 or antioxidant 168; Defoaming agent selected from silicone defoaming agent; Or one or more of catalysts, accelerators, anti-settling agents, lubricants, plasticizers, anti-aging agents, stabilizers, defoamers, leveling agents, and adhesives.
10. The preparation method according to claim 7, characterized in that In S3: After the extrusion process, it is subjected to biaxial stretching treatment, and the stretching temperature is the melting point of the polymer (T m ) below 30-50°C or glass transition temperature (T g ) above 50-100°C, and a stretching ratio of 2:1-5:1; The curing temperature of the tape casting process is 200-350°C, and the drying stage adopts a step-by-step temperature increase; The thickness of the calendering process is controlled at 0.2-3 mm by the roller spacing, and the vulcanization temperature is controlled at 100-180°C; The coating thickness of the coating process is controlled to 10 to 500 μm through spraying, scraping and dispensing parameters.
Citation Information
Patent Citations
Silicon nitride-aluminum nitride / polymer composite material and preparation method thereof
CN118359449A
Cited By
Super-long aluminum nitride fiber and self-generation combustion reactor high-flux preparation method thereof
CN121250591A